3-butyl-4-(3-methyl-3-phenylcyclobut-1-yl)-1,3-thiazole-2(3H)-thione - Kirilmis, C; Koca, M; Arici, C; Heinemann, FW; Ahmedzade, M (Int Union Crystallography, 2005)
In the title compound, C18H23NS2, the bond lengths and angles are unexceptional. The butyl chain is in a fully extended conformation. The dihedral angle between the thiazole and phenyl rings is 87.21 (2)degrees. The crystal structure is stabilized by one weak intramolecular C-H...S hydrogen bond.
Keywords: Antimicrobial Activity; Cyclobutane; Crystal